Impact of Online Marketing Tools on Online Shopping Behavior in India (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In this new era of the online world, marketing  tactics have transformed to grab the attention  of the customers and generate the concept  of online marketing. The aim of this study is  to determine the impact of online marketing  tools on the online shopping behavior of the  consumers in the current advanced technological  environment of India. Five online marketing  tools were considered: E-mail Marketing, Search  Engine Marketing, Social Media Marketing,  Display Advertising, and Mobile Advertising.  The sample size is 542 and data were collected  from New Delhi, Gorakhpur and Mumbai.  For determining the impact, multiple linear  regression is applied. S.P.S.S is used for analyzing  the data. All five online marketing tools have  a significant impact on the online shopping  behavior of consumers. E-mail marketing has  a substantial impact on consumer’s behavior  in online shopping. The marketer has first to  choose the right online marketing tool to use  and then evaluate that tool in terms of, how  much it contributes to the business.
Keywords: online marketing tools; internet marketing tools; internet